Role of dietary vitamin E in cadmium-induced oxidative damage in rabbit's blood, liver and kidneys - Beytut, E; Yuce, A; Kamiloglu, NN; Aksakal, M (Imr Press, 2003)
The aim of this work was to determine the effect of dietary vitamin E intake on lipid peroxidation (LPO) by measuring thiobarbituric acid reactive substances (TBARS), vitamin E and reduced glutathione (GSH) levels, and glutathione peroxidase (GSH-Px: EC 1.11.1.9) activity in plasma, red blood cells (RBC), livers, and kidneys of rabbits dosed with cadmium (Cd). Six-month-old clinically healthy New Zealand White rabbits (8 in each group) were given, tap water only, containing I g CdCl2/L, or tap water with CdCl2 plus vitamin E (100 mg dl-alpha-tocopheryl acetate in 0.2 mL corn oil) daily for 30 days. The vitamin E level in the plasma, liver, and kidneys was significantly higher in the control than in the Cd-only group, and TBARS levels were significantly lower. There were no statistical differences between the control and Cd-only groups GSH-Px activities and GSH levels in RBC, liver, and kidneys. Vitamin E levels in plasma, liver, and kidneys and GSH-Px activity in RBC were higher in the vitamin E group than in both control and Cd-only groups. However, the TBARS levels of RBC, liver, and kidneys in vitamin E administered group were decreased. Therefore, the present study demonstrates the effectiveness of vitamin E in reducing oxidative stress in Cd-treated rabbits and suggests that reductions in increased TBARS due to Cd toxicity may be an important factor in the action of vitamin E.
Keywords: cadmium; vitamin E; antioxidant; lipid peroxidation; erythrocyte; liver; kidney